Pelatihan Pembuatan Kuweh Adee Dengan Menggunakan Oven Sirib Untuk Peningkatan Perekonomian Di Pesantren Ruhul Falah Samahani Aceh Besar - Nazaruddin Nazaruddin; Yani Prihatina Eka Furda; Suprihadi; Rini Susiani; Fuady Fuady; Amir Mukhlis; Umar Umar (STIKes Ibnu Sina Ajibarang, 2023)
Dayah Ruhul Falah was founded in 2003 by Al Fadhil Tgk.H.Ibrahim Hasyim, established on 4500 m2 of waqf land with 800 students from various regions of Aceh such as North Aceh, Pidie, Aceh Besar and Banda Aceh. Along with the development of time and progress that is increasingly globalized, pesantren have not shown significant progress, this is because pesantren still have challenges ranging from management, the curriculum that is applied and the facilities owned are still very limited and the source of funds is minimal. The ability of pesantren managers to innovate is a requirement for efforts to direct changes in pesantren institutions to become more advanced in increasing and financial independence to make these changes. So far, the management of financial funds related to the activities carried out at Pasantren Ruhul Falah, both educators' honorariums and other needs in general, has been sourced from financing originating from the parents of students, government and private institutions. Pasantren Ruhul Falah, which was founded in 2003, has no pasanten-owned business entity managed under the pasantren, so it is necessary to conduct training and education for administrators and students in the dayah by making kueh, developing moringa leaves into the economy. This service activity was carried out with the aim of increasing knowledge and skills for training participants to become independent entrepreneurs. The method we do with lectures, questions and answers, practice and demonstrations and group exercises. This program begins with the preparation stage by forming a community service committee team by coordinating team members with the aim of making it easier to socialize to other university lecturers who want to join the community service group. In this community service, the target to be achieved is understanding and skills so that it can improve the economy in Pasantren Ruhul Falah Samahani Aceh Besar.